Respon Dinamis Kurs terhadap Tingkat Bunga di Indonesia - Rahmi, Nanda; Fachrurrozi, Kamal (Fakultas Ekonomi Universitas Samudra, 2021)
This study is to analyze the dynamic response of exchange rate to interest rate in Indonesia. Yearly data form 2002 to 2018 are used in this study and autoregressive model is utilized to capture dynamic response. The results show that the exchange rate has negative and significant response to interest rate. Furthermore, the effects of interest rate on exchange rate is higher in longrun than short-run. It is suggested to monetary authority to strength the domestic fundamental to achieve more effective of interest rate to stabilize the exchange rate fluctuations.